(3RGO GdeSjQ aj Yde GdJaSjQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3MSf Hf Ydi Hf eMeO Hf CHj HcQ GdMfai s)
(3ChdgG (B:s
(3JHJOF HChd ShQI GdCfYGe s
(3BNQgG (B:s
(3hJfJgi HBNQ ShQI GdESQGA s
(3eLdOI CNQi efgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B33 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B947s
Keywords: (3GdJaSjQ hYdhe GdbQBfs